La conciliación prejudicial contenciosa administrativa (2015)
The pretrial contentious-administrative settlement proceeding is one of the most effective and used alternative dispute resolution mechanisms in the legal system. Therefore, its evolution, legal and doctrinal developments, and the different Court rulings have taken place as part of a procedural requirement. The principles of celerity and economy are involved in order to help decongesting the backlog of cases in courts, hence, detracting complexity, effort, time and money to the administration of justice and determining whether the State and settlement authorities are fully trained to perform the conciliation procedure in the pretrial stage of the matters involved, which additionally, have procedural requirements. Through fair and equitable settlement agreements, faster, clear and economic changes aimed at resolving disputes that arise between the two parts are possible (Act 446/1998, Art. 64).